Evaluation of acitretin side effects on Iraqi psoriatic patients - H. Kadhim‎, Ahmed; A. Hassan‎, Dhia'a; H. Chyad‎, Amer; M. Khudyar‎, Abdulstaar (The Iraqi Journal of Veterinary Medicine, 2010)
Acitretin is the major metabolite of etretinate , an aromatic retinoid that formerly was approved for Psoriasis by exhibiting vitamin A activity. Acitretin was wildly used to improve plaque psoriasis and also for postural psoriasis and erthrodemic psoriasis .The present study focus on the evaluation of the common side effects of acitretin which makes a wide hesitation for Iraqi dermatologists to use it in treatement of psoriasis. Twenty psoriatic outpatient were treated with a dose of 25mg/ day for three continuous months in outpatient clinic of al- noor hospital during 2009 , their lipid profiles , liver and kidney function tests before starting treatment with acitretin considered as a control values. It was noticed that AST level increased significantly during 2nd and 3rd months of treatment and there is no significant change in S. Creatinine and BUN while TG increased significantly in 2nd and 3rd months of treatment.Cholesterol increased in the 3rd month of treatment. There is other important factors should be consider before evaluation the physiological changes may be caused by acitretin like smoking , alcohol intake , obesity and genetic association between psoriasis and other physiological change. However the changes that caused by administration of acitretin were relatively acceptable and not preventive measurement , but continuous monitoring (of TG , cholesterol , liver and kidney function test) still required regularly.